2003
DOI: 10.1053/jlts.2003.50131
|View full text |Cite
|
Sign up to set email alerts
|

The effect of liver graft-body weight ratio on the core temperature of pediatric patients during liver transplantation

Abstract: The left lateral segment of the liver from an adult living donor sometimes is relatively too large for a small pediatric recipient. It currently is unknown whether a high graft-recipient body weight ratio (GRWR) has a significant effect on core temperature during the anhepatic and reperfusion phases of living donor liver transplantation (LDLT). Seventy-two pediatric patients undergoing LDLT were divided into two groups according to body weight. Group I (GI) consisted of patients with a body weight greater than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 19 publications
(17 reference statements)
0
7
0
Order By: Relevance
“…The information for each patient was anonymized and deidentified before analysis. The general anesthesia, intraoperative monitoring and blood transfusion protocols used [9] , as well as their documentation [10] , were similar to those described in previously published reports [5,9,[11][12][13] . Estimated blood losses were made through visual estimations of a small (250 mL) suction bottle (Receptal ® Accurate Measurement Device, Hospira, Inc. Lake Forest, Il 60045, United States) and the weight of laparotomy sponges.…”
Section: Patient Selection and Data Collectionmentioning
confidence: 65%
See 1 more Smart Citation
“…The information for each patient was anonymized and deidentified before analysis. The general anesthesia, intraoperative monitoring and blood transfusion protocols used [9] , as well as their documentation [10] , were similar to those described in previously published reports [5,9,[11][12][13] . Estimated blood losses were made through visual estimations of a small (250 mL) suction bottle (Receptal ® Accurate Measurement Device, Hospira, Inc. Lake Forest, Il 60045, United States) and the weight of laparotomy sponges.…”
Section: Patient Selection and Data Collectionmentioning
confidence: 65%
“…The outcomes of such transplants for pediatric patients weighing less than 10 kg differ from those for pediatric patients weighing more than 10 kg [1][2][3][4] . We have previously reported that the average change in core temperature during an LDLT for pediatric patients weighing less than 10 kg is significantly different from that in heavier children [5] . Furthermore, a lower survival rate for lower weight children was reported by Arnon et al [3] , and according to other studies, this poorer survival results from higher risks of perioperative vascular complications, bile duct complications and infections [4,6,7] .…”
Section: Introductionmentioning
confidence: 86%
“…Although noted in both age groups, the sudden decrease in NT during the anhepatic and reperfusion phases has been found to correlate with GRWR only in pediatric patients [15]. Graft weight itself has no apparent correlation with NT in both adult and pediatric patients.…”
Section: Resultsmentioning
confidence: 99%
“…1 and Table 2). Further analysis showed that the degree of decrease in NT in children correlated with GRWR rather than the graft weight [15]. Although adult patients received heavier liver grafts, but the GRWR was significantly smaller when compared with that of the pediatric group (Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation